The effect of income-shifting aggressiveness on corporate investment - De Simone, Lisa; Klassen, Kenneth J.; Seidman, Jeri K. (Journal of Accounting and Economics, 2022)
We investigate whether international income-shifting aggressiveness affects local investments. Amid heightened scrutiny of international activities by tax authorities, firms can support income-shifting goals by locating investments consistent with reported income. As a consequence, we predict firms that aggressively shift income will make affiliate-level investment decisions less influenced by local investment opportunities than firms that do not aggressively shift income. We use affiliate-level data from multinational corporations to develop a firm-year proxy for the sensitivity of reported income to cross-border tax incentives. Results suggest firm-years with below-median income-shifting aggressiveness exhibit a typical responsiveness of local investments to investment opportunities, but firm-years with above-median income-shifting aggressiveness exhibit no statistical relation. Consistent with expectations, these results are stronger for firms with better governance or subject to greater tax authority scrutiny. Our tests extend the literature on investment distortions by documenting that multinational corporations’ international tax considerations alter their local tangible investment decisions.